Estudo de efeitos quânticos nas propriedades eletrônicas de nanofios semicondutores - Sousa-Dias, Mariama Rebello de (2010)
The growth and characterization of semiconductor nanowires systems have attracted increasing interest due to their potential technological application, like, photo-detectors, optoelectronic devices and their promising features for quantum information processing and photonic applications. The goal of this work is the characterization of properties of semiconductor nanowires. The study was started within the framework of classical electrodynamics and this model for light-scattering was contrasted with experimental results from the photoluminescence. This classical model has been published in the literature without a concrete discussion and its application range is often not compatible with the analyzed experimental phenomenology. Thus, we have introduced quantum elements to elucidate a consistent phenomenology with the results obtained in the experiments. Through the k.p method, using in particular the Luttinger Hamiltonian, the effects of biaxial confinement and strain were analyzed in the valence band of semiconductor nanowires. This study was complemented with the description of optical properties. For the conduction band states, we were able to introduce the spin-orbit interaction since analytical results, successfully obtained from the simulation of the valence band, could be directly used in this new calculation.